The Effect of Principal Communication Skills And Teacher Professionalism On Teacher Work Productivity At Tlogobodosari II Elementary School And Andonosari I State Elementary School Pasuruan Regency: Pengaruh Keterampilan Komunikasi Kepala Sekolah dan Profesionalisme Guru Terhadap Produktivitas Kerja Guru Di SD Negeri Tlogobodosari II Dan SD Negeri Andonosari I Kabupaten Pasuruan - Hermanoadi; Thohirin, Ahmad; A Faizin; Suyitno; Azizah, Anna Mussanatul (Procedia of Social Sciences and Humanities, 2022)
As a school leader, the principal must be able to lead, direct and supervise teachers, and carry out school activities that require good communication skills. Good and effective communication will be able to build cooperation between school principals and teachers; school principals can provide guidance to teachers; can direct and develop teacher performance so that teachers can improve their abilities and skills in teaching so that teachers are expected to increase their work productivity. Another factor that can affect teacher work productivity comes from within, namely teacher professionalism. With the existence of professional teachers, it is expected that teacher work productivity will also increase. This study aims to determine the effect of the principal's communication skills on the work productivity of teachers at SD Negeri Tlogobodosari II and SD Negeri Andonosari I; and knowing the influence of teacher professionalism on work productivity at SD Negeri Tlogobodosari II and SD Negeri Andonosari I. This type of research is a quantitative research where a questionnaire is given to all teachers who work at SD Negeri Tlogobodosari II and SD Negeri Andonosari I. The results showed that there was an influence of the principal's communication skills on the work productivity of teachers at SD Negeri Tlogobodosari II and SD Negeri Andonosari I which was carried out by means of criticism and suggestions; holding training/seminars; and motivation as indicated by the communication results of 91.00% and 89.75%, respectively, and the teacher's work productivity of 92.25% and 91.50%, respectively. In addition, there is also an influence of teacher professionalism on teacher work productivity at SD Negeri Tlogobodosari II and SD Negeri Andonosari I because if a teacher is a professional teacher then the teacher will have the ability, education, and skills in teaching so that it will increase teacher work productivity marked with the results of the distribution of teacher professionalism questionnaires of 89.75% and 89.00%, respective.